Interrupted inferior vena cava and partial anomalous pulmonary venous return with atrial septal defect in a 38-year-old adult: A case report - Colak, Mehmet Cengiz; Rahman, Ali; Kocaturk, Hasan; Bayram, Ednan; Kocakoc, Ercan (My University, 2009)
We present a woman having congenital anomalies of the inferior vena cava and partial anomalous pulmonary venous return from the right lung with atrial septal defect in a 38-year-old. Congenital anomalies of inferior vena cava are rare. They are seen more often in young males. If there are not other anomalies, they are latent for a long time. Peripheral venous thrombosis, chronic venous insufficiency, dyspnea and fatigue are often the first symptoms of these anomalies. Surgical repair of atrial septal defect with partial anomalous pulmonary venous return include provision of durably unobstructed systemic and pulmonary venous pathways, closure of the atrial septal defect, and avoidance of arrhythmias. The diagnosis has been determined by compression ultrasonography with color doppler assessment, multidetector computed tomography angiography and echocardiography. © 2009 Colak et al; licensee Cases Network Ltd.
Keywords: accessory spleen; adult; article; cardiomegaly; cardiopulmonary bypass; case report; diagnostic imaging; dyspnea; electrocardiography; fatigue; female; heart atrium septum defect; human; inferior cava vein; limb swelling; lung vein drainage anomaly; sternotomy; systolic heart murmur; vein insufficiency